LEGAL AND REGULATORY BASIS OF INCLUSIVE EDUCATION - Abdullayeva Feruza Boytumanovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the legal basis of inclusive education, the state of development of inclusive education abroad and in Uzbekistan, the action program for the disabled; Convention on the Rights of the Child; The World Declaration on Education, the UN Standard Provisions for Persons with Disabilities, and the Salamanca Declaration for Persons with Disabilities set the priority of inclusive education.